2008
DOI: 10.1111/j.1752-1688.2008.00230.x
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for Riparian Vegetative Shade Restoration Based Upon a Theoretical Shaded‐Stream Model1

Abstract: Guidelines for riparian vegetative shade restoration were developed using a theoretical model of total daily radiation received by a shaded stream. The model assumed stream shading by nontransmitting, vertical or overhanging, solid vegetation planes in infinitely long reaches. Radiation components considered in the model were direct beam shortwave on the stream centerline, diffuse atmospheric shortwave, shortwave reflected by vegetation, atmospheric longwave, and longwave emitted by vegetation. Potential or ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(58 citation statements)
references
References 49 publications
5
53
0
Order By: Relevance
“…Indeed the findings of Ghermandi et al (2009) and others (e.g. Davies-Colley and Quinn, 1998;Boothroyd et al, 2004;Caissie et al, 2007) are consistent with the Dewalle (2008) model but all these study sites are dissimilar to the Ouse, either in terms of latitude or river width. In the Ouse, the reduction in intensity of solar radiation reaching the water column due to tree shading was assumed to be 39%, as estimated using the method of DeWalle (2008).…”
Section: Scenario Analysissupporting
confidence: 71%
See 2 more Smart Citations
“…Indeed the findings of Ghermandi et al (2009) and others (e.g. Davies-Colley and Quinn, 1998;Boothroyd et al, 2004;Caissie et al, 2007) are consistent with the Dewalle (2008) model but all these study sites are dissimilar to the Ouse, either in terms of latitude or river width. In the Ouse, the reduction in intensity of solar radiation reaching the water column due to tree shading was assumed to be 39%, as estimated using the method of DeWalle (2008).…”
Section: Scenario Analysissupporting
confidence: 71%
“…Davies-Colley and Quinn, 1998;Boothroyd et al, 2004;Caissie et al, 2007) are consistent with the Dewalle (2008) model but all these study sites are dissimilar to the Ouse, either in terms of latitude or river width. In the Ouse, the reduction in intensity of solar radiation reaching the water column due to tree shading was assumed to be 39%, as estimated using the method of DeWalle (2008). The method calculates shading as a function of site latitude, river flow direction and the ratio of the height of the riparian vegetation to the width of the riverbank.…”
Section: Scenario Analysissupporting
confidence: 63%
See 1 more Smart Citation
“…our simulations indicated that shading of streams depends strongly on stream size, because the ratio of canopy height to stream width is the single most important factor controlling stream light exposure (Davies-Colley & Rutherford 2005;DeWalle 2008). as a consequence, small streams in which thermal regime is most severely disrupted by light exposure following riparian clearance, recover most rapidlybecause trees growing on their banks rapidly achieve occlusion of a large proportion of the canopy gap.…”
Section: Stream Conditionsmentioning
confidence: 99%
“…However, the height and density of the riparian vegetation have an equal or even higher impact on water temperature (Sridhar et al, 2004;DeWalle, 2010). DaviesColley et al (2009) andDeWalle (2008) showed that the ratio of canopy height to stream width has particular high influence on stream light exposure and is therefore notably relevant.…”
Section: Introductionmentioning
confidence: 99%